Why Translate Science? : Documents from Antiquity to the 16 Th Century in the Historical West (Bactria to the Atlantic). - Gutas, Dimitri (Boston : BRILL, 2022)
A collection of documents from antiquity to the 16th century in the historical West (Bactria to the Atlantic), in the original languages with an English translation and introductory essays, about the motivations and purposes of translation from and into Greek, Syriac, Middle Persian, Arabic, Hebrew, and Latin, as given in the personal statements by the translators, scholars, and historians of each society.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2024. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Electronic books